1990
DOI: 10.1021/jm00171a015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of substituted 7,12-dihydropyrido[3,2-b:5,4-b']diindoles: rigid planar benzodiazepine receptor ligands with inverse agonist/antagonist properties

Abstract: A series of 1-, 2-, 3-, 4-, 5-, 6-, 7-, 10-, and 12-substituted pyridodiindoles were synthesized and screened in vitro against [3H]diazepam for activity at the benzodiazepine receptor (BzR). In vitro, the 2-substituted pyridodiindoles were found to be the most potent (IC50 less than 10 nM) of this new class of BzR ligands. In vivo, 2-methoxypyridodiindole 19a (IC50 = 8 nM) was found to be the most potent partial inverse agonist (proconvulsant) of the series. The parent compound 2 (IC50 = 4 nM) was only slightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 5 publications
0
43
0
Order By: Relevance
“…Binding affinity studies at the BzR, performed in bovine brain membranes through displacement experiments with the radiolabelled antagonist [ 3 H]Ro 15-1788, (Table (1)), clearly emphasized the key pharmacophoric role of the N(10)-H group, postulated as a hydrogen bond donor site. Actually, the insertion of a methyl group in this position, as in (18)(19)(20)(21)(22), dramatically lowered efficacy, and with the exception of (18), showing a K i value of 860 nM, all the substituted compounds were devoid of any binding affinity. Within the (5-17) series, the presence of an aromatic ring in position 3 seemed mandatory for an appreciable efficacy, as both the 3-H derivative, (5), and the 3-CH 3 -substituted (6) showed no binding affinity.…”
Section: [124]triazino[43-a]benzimidazol-4(10h)-ones (Tbis)mentioning
confidence: 97%
See 2 more Smart Citations
“…Binding affinity studies at the BzR, performed in bovine brain membranes through displacement experiments with the radiolabelled antagonist [ 3 H]Ro 15-1788, (Table (1)), clearly emphasized the key pharmacophoric role of the N(10)-H group, postulated as a hydrogen bond donor site. Actually, the insertion of a methyl group in this position, as in (18)(19)(20)(21)(22), dramatically lowered efficacy, and with the exception of (18), showing a K i value of 860 nM, all the substituted compounds were devoid of any binding affinity. Within the (5-17) series, the presence of an aromatic ring in position 3 seemed mandatory for an appreciable efficacy, as both the 3-H derivative, (5), and the 3-CH 3 -substituted (6) showed no binding affinity.…”
Section: [124]triazino[43-a]benzimidazol-4(10h)-ones (Tbis)mentioning
confidence: 97%
“…(4). Different substitution patterns were explored in positions 3 of the heterocyclic core, (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and some of them were combined with methylation at position 10, (18)(19)(20)(21)(22), to deduce some useful SARs for this novel class of rigid BzR ligands. Binding affinity studies at the BzR, performed in bovine brain membranes through displacement experiments with the radiolabelled antagonist [ 3 H]Ro 15-1788, (Table (1)), clearly emphasized the key pharmacophoric role of the N(10)-H group, postulated as a hydrogen bond donor site.…”
Section: [124]triazino[43-a]benzimidazol-4(10h)-ones (Tbis)mentioning
confidence: 99%
See 1 more Smart Citation
“…The model has recently been applied for the identification and optimization of novel 4-quinolones and azaflavone derivatives as ligands at the GABA A receptors, with affinities as low as 0.05 nM [9][10][11]. In addition, several other classes of compounds are known to bind to the benzodiazepine site, such as the 2-arylpyrazoloquinolines [12,13], -carbolines [14], pyridodiindoles [15], pyrimidin-5(6H)-ones [16], cyclopyrrolones and quinolines [17]. In the present investigation new azoloquinolones, 3-arylisothiazolo [5,4-b]quinolin-4(9H)-ones and 3-arylisoxazolo [5,4-b]quinolin-4(9H)-ones, have been designed using the pharmacophore model, prepared by synthesis, and assayed.…”
Section: Introductionmentioning
confidence: 99%
“…The BZD binding sites in the brain were identified and described by radioligand receptor binding assays and originally it was found that only 1,4-BZD derivatives bind to these receptors. It has since been shown that many groups of compounds bind to the BZD receptor with high affinity, e. g., triazolopyridazines, cyclopyrrolones, quinolines and β-carbolines [4][5][6][7]. Several pharmacophore models have been proposed for BZDs, and amongst all models suggested for binding to the BZD receptor at least two features are common: an aromatic ring and a coplanar proton accepting group in suitable distance (5A o ).…”
Section: Introductionmentioning
confidence: 99%